Short-term mortality of patients with saddle pulmonary embolism: A single-center study - Reza Hajizadeh; Samad Ghaffari; Hamid Rajebi; Hadiseh Kavandi; Elnaz Javanshir; Golshan Fahimi; Sahar Ghodratizadeh (KARE Publishing, 2019)
Objective: Although hemodynamic instability has been identified as the most established mortality predictor in acute pulmonary embolism (PE), the debate is still open about the prognostic significance of saddle pulmonary embolism (SPE). This study determined the in-hospital mortality rate of SPE patients diagnosed via computed tomographic pulmonary angiography (CTPA) and compared these cases with non-SPE patients. Methods: The presence of SPE observed on CTPA was used to classify 492 consecutive patients into SPE and non-SPE groups. Different features were compared between the 2 groups, and independent predictors of in-hospital mortality in acute PE were identified. Results: A total of 70 patients (14.2%) had SPE. In univariate analysis, the SPE group was seen to have a higher in-hospital mortality rate, as well as a lower oxygen saturation level and systolic and diastolic blood pressure in comparison with the non-SPE group (all p values <0.005). Multivariate analysis revealed that SPE was an independent predictor of in-hospital mortality in acute PE patients (Odds ratio: 9.21, 95% confidence interval: 3.40-24.89; p value <0.001). Conclusion: The results of this study indicated that SPE had a statistically significant importance in predicting in-hospital mortality and adverse events in PE patients. These findings were not consistent with many prior studies.